EXTRACTION AND APPLICATION OF SOME NATURAL FLOWER PIGMENTS AS ACID-BASE INDICATORS - Gwarzo, Dahiru Adamu; Suleiman, Jibrin Sabo; Idriss, Ibrahim Musa (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, the pigments of Ixora coccinea, Lantana camara, Moringa oleifera, Nerium oleander, and Sensevieria trifasciata were used to identify the natural indicators for acid-base titrations using 0.1% acidified ethanolic solvent. The Potiskum Vetenary, biological gardens of Federal University Gashua and Umar Suleiman College of Education Gashua were used to collect the samples. All three types of acid-base titrations—strong acids against strong bases, strong acids against weak bases, and weak acids against strong bases—were studied. Calculations were made for the indicator's color change, the pH at the relevant point and the average titre values for each type of acid-base titration. According to the data, there was no appreciable difference between the mean titre values of methyl orange and Ixora c. flower extract in strong acid against weak base. Moringa o. flower extract can be used in place of methyl orange and phenolphthalein for strong acid against strong base, strong acid against weak base and weak acid against strong base titrations. Nerium o. flower extract can be used in place of phenolphthalein in weak acid against strong base titrations. Sensevieria t. flower extract can be used in place of methyl orange in strong acid against weak base titrations and phenolphthalein for strong acid against strong base and weak acid against strong base titrations. In all acid-base titrations, lantana c. flower extract had no discernible reaction. Most of the extracts proved to be a good substitute for synthetic acid-base indicators. Using these harmless and readily available flowers is recommended.
Keywords: Flower pigments; acid-base indicators; extraction; health hazards; anthocyanins; flavonoids